Ice-nucleating particles in northern Greenland: annual cycles, biological contribution and parameterizations - K. C. H. Sze; H. Wex; M. Hartmann; M. Hartmann; H. Skov; A. Massling; D. Villanueva; F. Stratmann (Atmospheric Chemistry and Physics, 2023)
Ice-nucleating particles (INPs) can initiate ice formation in clouds at temperatures above −38 ∘C through heterogeneous ice nucleation. As a result, INPs affect cloud microphysical and radiative properties, cloud lifetime, and precipitation behavior and thereby ultimately the Earth's climate. Yet, little is known regarding the sources, abundance and properties of INPs, especially in remote regions such as the Arctic. In this study, 2-year-long INP measurements (from July 2018 to September 2020) at Villum Research Station in northern Greenland are presented. A low-volume filter sampler was deployed to collect filter samples for offline INP analysis. An annual cycle of INP concentration (NINP) was observed, and the fraction of heat-labile INPs was found to be higher in months with low to no snow cover and lower in months when the surface was well covered in snow (> 0.8 m). Samples were categorized into three different types based only on the slope of their INP spectra, namely into summer, winter and mix type. For each of the types a temperature-dependent INP parameterization was derived, clearly different depending on the time of the year. Winter and summer types occurred only during their respective seasons and were seen 60 % of the time. The mixed type occurred in the remaining 40 % of the time throughout the year. April, May and November were found to be transition months. A case study comparing April 2019 and April 2020 was performed. The month of April was selected because a significant difference in NINP was observed during these two periods, with clearly higher NINP in April 2020. In parallel to the observed differences in NINP, also a higher cloud-ice fraction was observed in satellite data for April 2020, compared to April 2019. NINP in the case study period revealed no clear dependency on either meteorological parameters or different surface types which were passed by the collected air masses. Overall, the results suggest that the coastal regions of Greenland were the main sources of INPs in April 2019 and 2020, most likely including both local terrestrial and marine sources.